The protective potency of probiotic bacteria and their microbial products against enteric infections-review - Koninkx, J F J G; Malago, J J (Folia microbiologica, 2008)
The intestinal environment accommodates a wide range of contents ranging from harmless beneficial dietary and microbial flora to harmful pathogenic bacteria. This has resulted in the development of highly adapted epithelial cells lining the intestine. This adaptation involves the potential of crypt cells to proliferate and to constantly replace villous cells that are lost due to maturity or death. As a result, the normal intestinal epithelial integrity and functions are maintained. This phenomenon is eminent in intestinal defense whereby the intestinal epithelial cells serve as a physical barrier against luminal agents. The protection against agents in the gut lumen can only be effective if the epithelium is intact. Restitution of the damaged epithelium is therefore crucial in this type of defense.
Keywords: gastrointestinální nemoci; Probiotics; Intestines; Gastrointestinal Diseases; Bacterial Infections; Heat-Shock Proteins; Caco-2 buňky; lidé; bakteriální infekce; antibióza; Epithelial Cells; střeva; Bacteria; probiotika; Caco-2 Cells; epitelové buňky; proteiny teplotního šoku; Antibiosis; Humans